The effects of adequate and excessive application of mineral fertilizers on the soil - Bijay-Singh; Sapkota, Tek Bahadur (Elsevier, 2023)
Fertilizers increase availability of essential plant nutrients in the soil and alter many chemical, biological and physical soil properties. Fertilizers lead to the accumulation of soil organic matter (SOM), but the excessive application of nitrogen fertilizers is deleterious to SOM, may contribute to nitrate pollution of freshwaters and emission of nitrous oxide – a greenhouse gas. Nitrogen fertilizers can also cause soil acidification. Phosphatic fertilizers may contribute to eutrophication of surface waters, and heavy metal impurities in these may contaminate soils. Balanced fertilization positively affects soil organic matter and soil biota; and in general soil microbial life is positively influenced.